TRANSFORMATION OF ISLAMIC EDUCATION FROM MARGINAL MAKKAH TO CIVILIZED MADINAH - Ridwan Hadi Wijaya; Eva Dewi; Zainudin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The transformation of Islamic education from the marginal phase in Mecca to the civilized phase in Medina brought significant changes. In Mecca, education was carried out in secret due to pressure. In Medina, organized educational centers such as the Nabawi Mosque and Kuttab were formed. The curriculum becomes more systematic with varied teaching methods. The number of teachers and students increased. Education includes religious and general knowledge, as well as character formation. This transformation has an impact on the spread of Islam more effectively, the formation of a strong Muslim society, the development of science, and tolerance between people. This experience provides valuable lessons for contemporary Islamic education.